(3GdHWGdI hGdeLJeY GdeUQi ai GdfUa GdGhd ef GdbQf GdYTQjf (B1918- 1952/ s - (3SeGM EHQGgje ZQjH GdTQj`a s; (3CMeO GdTQHjfi (B: s; (3eMeO ceGd GdJGHYi (B: s ((3GdbGgQI (B: s (3SeGM EHQGgje ZQjH GdTQj`a (B: s, 2016)
(3JfGhdJ GdQSGdI eTcdI GdHWGdI HTbjgG GdQjaj hGdMVQj aj GdfUa GdChd ef GdbQf GdYTQjf(B: (3NdGd GdaJQI ef (B1918 (3Edi (B1952: (3ef NdGd SQO ThGgOgG hJMdjd CSHGHgG(B: (3hfJGFLgG Ydi GdeLJeY GdeUQj aj Jdc GdaJQI(B: (3MjK JYQV GdeLJeY GdeUQj ccd deLehYI ef GdCReGJ GdGbJUGOjI GdfGJLI Yf GdMQH GdYGdejI GdChdi(B: (3hCReI GdcSGO GdYGdej(B: (3hGdMQH GdYGdejI GdKGfjI(B: (3hhLhO GdGMJdGd GdHQjWGfj aj eUQ(B: (3eeG CKQ SdkHG Ydi JhGaQ aQU GdYed aj GdQja hGdeOf Ydi MO ShGA(B: (3ceG cGf ShA JhRjY GdCQGVj GdRQGYjI heMOhOjJgG ebGQfI HRjGOI GdScGf (B: (3hJMce cHGQ GdedGc aj ebOQGJ GdCehQ aj GdQja Cge CSHGH GdNdd aj Shb GdYed GdRQGYj(B: (3hJBcd WHbI UZGQ GdedGc(B: (3hJMhdge Edi eYOejf HYOeG YLRhG Yf MeGjI CQGVjge ef GdHjY GdLHQj haGA ddOjhf(B: (3hbO cGf dgPg GdChVGY CShA GdCKQ Ydi GdMGdI GdGbJUGOjI hGdGLJeGYjI hGdCefjI aj eUQ(B: (3hbO MGhdJ GdMcheGJ GdeJYGbHI GdSjWQI Ydi gPg GdeTcdI HeLehYI ef GdELQGAGJ GdJj de JSJWY GdbVGA YdjgG hHbi GdeLJeY GdeUQj aj eLedI jYGfi ef GdHWGdI hGdabQ hGdXde GdGLJeGYj MJi bjGe KhQI jhdjh (B1952.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdJGQjNs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdHWGdI s; (3GdHWGdI GdebfYI aj GdeOf s; (3UZGQ edGc GdCQGVj GdRQGYjI s